Failure Physics and Reliability of GaN‐Based HEMTs for Microwave and Millimeter‐Wave Applications: A Review of Consolidated Data and Recent Results. Issue 24 (19th November 2022) - Zanoni, Enrico; Rampazzo, Fabiana; De Santi, Carlo; Gao, Zhan; Sharma, Chandan; Modolo, Nicola; Verzellesi, Giovanni; Chini, Alessandro; Meneghesso, Gaudenzio; Meneghini, Matteo
Abstract : Herein, the results are reviewed concerning reliability of high‐electron mobility transistors (HEMTs) based on GaN, which currently represent the technology of choice for high‐efficiency microwave and millimeter‐wave power amplifiers. Several failure mechanisms of these devices are extensively studied, including converse piezoelectric effects, formation of conductive percolation paths at the edge of gate toward the drain, surface oxidation of GaN, time‐dependent breakdown of GaN buffer, and of field‐plate dielectric. For GaN HEMTs with scaled gate length, the simultaneous control of short‐channel effects, deep‐level dispersion, and hot‐electron‐induced degradation requires a careful optimization of epitaxial material quality and device design. Abstract : Herein, the reliability of GaN‐based high‐electron‐mobility‐transistors are reviewed. Several failure mechanisms are studied, including converse piezoelectric effects, formation of conductive percolation paths at the gate edge, surface oxidation of GaN, time‐dependent breakdown of GaN buffer, and of field‐plate dielectric. The simultaneous control of short‐channel effects, deep‐level dispersion, and hot‐electron‐induced degradation requires a careful optimization of epitaxial material quality and device design.